Quantitative immunocytochemical characterization of mononuclear phagocytes. II. Monocytes and tissue macrophages. - Nibbering, P H (1987)
The purpose of the present study was to compare the monoclonal antibody (Mab) binding patterns of various tissue macrophages with each other and with blood monocytes. To allow recovery from the effects of the isolation procedure, or to obtain purified populations, macrophages were cultured for 24 hr and 48 hr. For comparison, blood monocytes were also cultured for 24 hr and 48 hr. Mab binding to individual cells, detected by the biotin avidin immunoperoxidase method, was quantified cytophotometrically and the results expressed as the median of the specific mean absorbance per 0.25 micron2 cell surface area or as specific integrated absorbance per cell. Analysis of the quantitative data in relation to the results of subjective evaluation of the peroxidase reaction product, demonstrating Mab binding to cells, yielded three classes for description of the intensity of antigen expression by cells: weak (specific mean absorbance per unit cell surface less than 0.07), moderate (values between 0.07 and 0.14), and intense (values more than 0.14). No matter how the results were expressed, comparison of the Mab binding patterns of macrophages with those of blood monocytes showed that spleen macrophages bound significantly less F4/80 and more M5/114 (Ia antigen). Kupffer cells and skin macrophages bound either approximately the same amount or considerably less of the various Mabs than monocytes did. Pulmonary tissue and alveolar macrophages bound significantly more 30.G.12 (leucocyte antigen), M3/38 (Mac-2 antigen), and M3/84 (Mac-3 antigen) and comparable amounts or considerably less of the other Mabs than the monocytes did. Peritoneal macrophages bound significantly more F4/80, M1/70 (complement receptor III), and 2.4.G.2. (Fc receptor II) and comparable amounts or considerably less of the other Mabs than monocytes did. It is concluded that macrophages from different organs and different anatomical sites within one organ differ from one another, for example, peritoneal macrophages do not resemble any other population of macrophages and alveolar macrophages do not resemble pulmonary tissue macrophages, and differentiation of blood monocytes into tissue macrophages does not show a distinct pattern.